2015
DOI: 10.1097/md.0000000000001227
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke-Associated Pneumonia With Acid-Suppressive Drugs

Abstract: Acid-suppressive drugs, including histamine-2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs), are common medications used for treating upper gastrointestinal tract disorders. However, acid-suppressive drugs have been reported to increase the risk of pneumonia in numerous disease populations. However, the relationship between acid-suppressive drugs and stroke-associated pneumonia (SAP) remains controversial.The purpose of this study was to investigate the association between acid-suppressive dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…The nonsignificant association between H2B and pneumonia demonstrated by our study agrees with previous studies [7, 8], which failed to find a significant association between H2B and pneumonia in acute stroke, although the power was insufficient in one study [7], and not described in the other [8]. Our study was designed with sufficient power to detect a two-fold increase in pneumonia by H2B, and the upper limit of the 95% CI of the RR was about 1.8.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The nonsignificant association between H2B and pneumonia demonstrated by our study agrees with previous studies [7, 8], which failed to find a significant association between H2B and pneumonia in acute stroke, although the power was insufficient in one study [7], and not described in the other [8]. Our study was designed with sufficient power to detect a two-fold increase in pneumonia by H2B, and the upper limit of the 95% CI of the RR was about 1.8.…”
Section: Discussionsupporting
confidence: 93%
“…The similarity in results indicates that use of PPI is indeed associated with an increased risk of pneumonia in acute stroke patients, as observed in other disease populations [10, 12, 13]. Nonetheless, such findings apparently disagree with a study using national insurance claims data in Taiwan [8] that failed to demonstrate the association between PPI and pneumonia in acute stroke patients. The negative result may be due to differences in the definition of exposure, which was at least one use of PPI use during the follow-up.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…GERD is considered to be a risk factor for COPD exacerbations and this can further increase the mortality in this group of patients (73). The use of acid suppressing agents (histamine-2 receptor antagonists and proton pump inhibitors) which are commonly used in GERD are associated with an increased risk of stroke-associated pneumonia (SAP) (74,75). The compromised immune state and the use of corticosteroids already puts COPD patients at higher risk for pneumonia (76).…”
Section: Impact Of Stroke On Copd Outcomesmentioning
confidence: 99%
“…Previous studies have reported that proton pump inhibitors (PPIs) are positively associated with the risk of community-acquired pneumonia (CAP) for various disease and age populations [3][4][5][6][7][8] , but the letter mentioned, "The author of the manuscript has not clearly described or validated the swallowing test in these dementia patients. Swallowing problems are the one of most common causes of pneumonia.…”
Section: Reply To: Proton Pump Inhibitors and Risk Of Pneumonia In Inmentioning
confidence: 99%